2020
DOI: 10.1152/ajpregu.00079.2019
|View full text |Cite
|
Sign up to set email alerts
|

Sensory signals mediating high blood pressure via sympathetic activation: role of adipose afferent reflex

Abstract: Blood pressure regulation in health and disease involves a balance between afferent and efferent signals from multiple organs and tissues. Although there are numerous reviews focused on the role of sympathetic nerves in different models of hypertension, few have revised the contribution of afferent nerves innervating adipose tissue and their role in the development of obesity-induced hypertension. Both clinical and basic research support the beneficial effects of bilateral renal denervation in lowering blood p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 183 publications
1
15
0
Order By: Relevance
“…8,9 The rostral ventrolateral medulla (RVLM), caudal ventrolateral medulla (CVLM), nucleus tractus solitarius (NTS), and paraventricular nucleus (PVN) are important central sites that control the sympathetic outflow. 10,11 Among them, the RVLM oblongata region contains neurons that receive inputs from various sources, playing a predominant role in controlling sympathetic vasomotor tone and blood pressure. 12 Zhang et al 13 concluded that PLIN2 knockdown in RVLM could block oxidative/nitrosative stress, alleviate sympathetic overdrive, and suppress SIH progression.…”
mentioning
confidence: 99%
“…8,9 The rostral ventrolateral medulla (RVLM), caudal ventrolateral medulla (CVLM), nucleus tractus solitarius (NTS), and paraventricular nucleus (PVN) are important central sites that control the sympathetic outflow. 10,11 Among them, the RVLM oblongata region contains neurons that receive inputs from various sources, playing a predominant role in controlling sympathetic vasomotor tone and blood pressure. 12 Zhang et al 13 concluded that PLIN2 knockdown in RVLM could block oxidative/nitrosative stress, alleviate sympathetic overdrive, and suppress SIH progression.…”
mentioning
confidence: 99%
“…193 These alterations in BP regulation are thought to be mediated via signaling within the paraventricular nucleus. 195,196 For more information related to these mechanisms, we direct the reader to recent a review on the adipose afferent reflex 197 in obesityrelated hypertension.…”
Section: Obesitymentioning
confidence: 99%
“…The activation of this sympatho-excitatory reflex in PRAT, AAR, can elevate sympathetic nerve activity and blood pressure ( 48 , 49 ). The effect of the sympathetic innervation was even greater in hypertensive rat models or following a high fat diet ( 48 , 49 ). Additionally, PRAT through AAR could regulate the sympathetic flow and therefore the cardiovascular system ( 50 ).…”
Section: Perirenal Adipose Tissue Physiologymentioning
confidence: 99%
“…The afferent nerves in the adipocytes controlling the sympathetic outflow are referred to as an adipose afferent reflex (AAR) that modulates local homeostasis regulating energy balance and lipolysis (45)(46)(47). The activation of this sympatho-excitatory reflex in PRAT, AAR, can elevate sympathetic nerve activity and blood pressure (48,49). The effect of the sympathetic innervation was even greater in hypertensive rat models or following a high fat diet (48,49).…”
Section: Perirenal Adipose Tissue Physiology Sympathetic Innervationmentioning
confidence: 99%